Draft Five Year Plan 1978-83 Area Development Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
The Tawa irrigation project aims at providing assured irrigation to 2.44 lakh hectares of land in Hoshangabad district and will ultimately irrigate 3.19 lakh hectares of cropped area in the Kharif, Rabi and summer seasons. The Left Bank Canal (LBC) will provide irrigation to 1.84 lakh hectares, while the Right Bank Canal will irrigate 0.60 lakh hectares of land in the command area.
Government of Madhya Pradesh, Planning, Economics and Statistics Department